2005
DOI: 10.1051/forest:2004085
|View full text |Cite
|
Sign up to set email alerts
|

Sicily represents the Italian reservoir of chloroplast DNA diversity of Quercus ilex L. (Fagaceae)

Abstract: -Chloroplast DNA polymorphism was analysed in forty-four Italian holm oak populations. Results obtained with different markers (PCR-RFLP and SSR) were congruent, showing a clear geographic structure of genetic diversity and high value of genetic differentiation (G ST = 0.80). By combining PCR-RFLP and SSR, eight haplotypes were identified in Italy, six of them in Sicily. Most populations were fixed for one haplotype. Some populations from the extreme West Mediterranean (Morocco) and the extreme East Mediterran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
2
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
0
15
2
3
Order By: Relevance
“…The presence of two chlorotypes of Q. ilex in Kessra (Siliana) can be explained by Two hypotheses: (i) these chlorotypes are different for each other and constituted two different taxonomic genera such as Quercus rotundifolia and Q. ilex species; (ii) One taxonomic genus diverged and gave these two different chlorotypes of Q. ilex which are represented by two infra-specific taxonomic ranks. The number of chlorotypes described in Tunisia is lower than that registered in Italy (Fineschi et al, 2005).…”
Section: Identification Of Chlorotypes In Quercus Ilex (I1 and I2)contrasting
confidence: 55%
“…The presence of two chlorotypes of Q. ilex in Kessra (Siliana) can be explained by Two hypotheses: (i) these chlorotypes are different for each other and constituted two different taxonomic genera such as Quercus rotundifolia and Q. ilex species; (ii) One taxonomic genus diverged and gave these two different chlorotypes of Q. ilex which are represented by two infra-specific taxonomic ranks. The number of chlorotypes described in Tunisia is lower than that registered in Italy (Fineschi et al, 2005).…”
Section: Identification Of Chlorotypes In Quercus Ilex (I1 and I2)contrasting
confidence: 55%
“…Ecosystem restoration is an issue of major concern to forest management in Sicily 280 and, regarding Quercus ilex genetic resources, priority has to be given to a 281 conservation forestry to preserve the specific genetic diversity found in Sicilian 282 populations [11,28,31]. Quite the contrary, the results of this study showed an 283 overall significant reduction of genetic diversity and a significant difference in 284 genetic composition of seedling lots in comparison with the natural seed origin stand.…”
contrasting
confidence: 54%
“…Although the presence of usual phylogeographic breaks does not exclude co-differentiation between Heligmosomoides and its host, co-differentiation might not be the most likely cause of these interruptions. In contrast, other phylogeographic breaks shared by Heligmosomoides and A. sylvaticus in South Western Europe do not correspond to phylogeographic breaks typically found in many other taxa: i.e., the differentiation of Sicily from continental Italy (even if few studies showed that Sicily is a hotspot of biodiversity in Europe (Randi et al, 2003;Fineschi et al, 2005;Fritz et al, 2005)), and the differentiation of Maghreb populations from Spain. These shared specific phylogeographic breaks are, in contrast to usual phylogeographic fractures, good clues arguing for long-term co-differentiation between the two species (Thompson, 2005).…”
Section: Regional Co-differentiation Between Heligmosomoides and A Smentioning
confidence: 68%